Assessing the clinical ethical competence of undergraduate medical students. - Mitchell, K R (1993)
At the University of Newcastle, health law and ethics is taught and assessed in each year of the five-year curriculum. However, the critical question for assessment remains: 'Does teaching ethics have a measurable effect on the clinical activity of medical students who have had such courses?' Those responsible for teaching confront this question each year they sit down to construct their assessment tools. Should they assess what the student knows? Should they assess the student's moral reasoning, that is, what decisions the student makes, and, how these decisions are justified, or should they assess what the student actually does when dealing with patients in the clinical setting, and how he or she does it? From 1982 to 1991, assessment at Newcastle was primarily aimed at determining the quality of the students' ethics knowledge base. This paper describes the strengths and limitations of a purely knowledge-based method of evaluation and why in 1992, we are now attempting to redefine and assess, what we call 'clinical ethical competence' in terms of how students actually apply this knowledge base in a controlled clinical context.